2005
DOI: 10.1002/jso.20220
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in sentinel node navigation for gastric cancer: A paradigm shift of surgical management

Abstract: The sentinel node (SN) is defined as the first draining node from the primary lesion and it has proven to be a good indicator of the metastatic status of regional lymph nodes in solid tumors. In the past 5 years, the validity of SN concept for gastric cancer has been demonstrated by a number of single institutional studies. Using a dual tracer method as the optimal procedure, the radio-guided method allows us to confirm the complete harvest of SNs by gamma probing, while the dye procedure enables us to perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
82
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 21 publications
1
82
0
11
Order By: Relevance
“…SN are defined as the first lymph nodes to receive lymphatic flow from primary tumor sites. Many investigators have already demonstrated the clinical utility of sentinel node navigation surgery (SNNS) for patients with gastric cancer,7, 8, 9, 10, 11 and the current technical procedures for SNNS have been gradually advancing over time. Furthermore, intraoperative methods have been developed for the accurate diagnosis of lymph node metastasis, including micrometastasis 12.…”
Section: Introductionmentioning
confidence: 99%
“…SN are defined as the first lymph nodes to receive lymphatic flow from primary tumor sites. Many investigators have already demonstrated the clinical utility of sentinel node navigation surgery (SNNS) for patients with gastric cancer,7, 8, 9, 10, 11 and the current technical procedures for SNNS have been gradually advancing over time. Furthermore, intraoperative methods have been developed for the accurate diagnosis of lymph node metastasis, including micrometastasis 12.…”
Section: Introductionmentioning
confidence: 99%
“…There have been initiatives that use SLNB in humans for gastric cancer aimed to indicating more economic lymphadenectomies and gastric resections 15,18,19,24,25 , and this conduct is currently becoming accepted in global clinical practice 9,11,26 , especially after the recommendation of the Japanese multicenter trial on the use of SLNB in early gastric cancer (T1 or T2, N0, M0) 27 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, SLNB has also been carried out for cases of early gastric cancer 5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations